The impact of Toll-like receptors on the immune system functioning and on the immunopathogenesis of chronic hepatitis C: a modern view (literature review) - L. M. Syzova; T. I. Koval; V. I. Ilchenko; I. M. Zviaholska; О. M. Iziumska (Zaporozhye State Medical University, 2020)
There exists a considerable body of literature on immunopathogenesis of chronic hepatitis C. Although results appear consistent with prior research in the area mentioned above, they appear inconsistent with the issues in the area of diagnosis, prognosis and treatment effectiveness. In this context the study addresses the research to receptors of the innate immune system - Toll-like receptors. The aim of the research is to analyze the data of current professional literature regarding the role of individual Toll-like receptors in the immunopathogenesis of chronic hepatitis C. Materials and methods. The method of reviewing and systematizing as well as the method of content analysis were used to overview the scientific literature as for the role of Toll-like receptors. For this purpose, we employ survey data collected from the world professional literature and analyzed the results of current researches. Conclusions. The innate immune system plays a prominent role in the primary protection of the body against pathogens which recognition depends on the Toll-like receptors family wheres the genetic analysis is considered as a promising method of preventive and personalized medicine. The advantage of genetic markers regardless of age and other factors contain information about the susceptibility to multifactorial diseases which can be used to create a «genetic passport» of a person. Perceptions about the impact of the Asp299Gly polymorphism of the Toll-like receptor 4 gene and Gln11Leu of the Toll-like receptor 7 gene on the immunopathogenesis of chronic hepatitis C are ambiguous and this research provides a good starting point for discussion and further study which will allow optimizing the therapeutic and diagnostic tactics for this disease based on the complex evaluation of immunity which are defined by the determined polymorphisms.